PENGEMBANGAN MODEL PEMBELAJARAN EKONOMI BERKARAKTER PANCASILA MELALUI MODEL ECONOMICS COOPERATIVE LEARNING - Nailariza Umami; Maria Aghata Sri Widyanti Hastuti (Jurnal Pendidikan Edutama, 2020)
Abstract: This research was conducted with the aim to develop a model of economic learning with national character with a design-based research (DBR) approach. This research used the Design Based Research approach in developing Economic Learning with Nationality Characteristics Through the Economic Cooperative Learning Model. The data analysis technique used is quantitative with descriptive and qualitative statistical techniques. Based on the results of research and development shows the results of responses of students at the time of trial at Blitar Muhammadiyah High School and in Rejotangan 1 Public High School at 91% and 95.3%. This means that the Cooperative Learning Economics model can make students understand about economic concepts that are in accordance with the ideology of the Indonesian Nation, especially able to instill national character values including love of Indonesian products, upholding togetherness, respecting other people's opinions, saving, wise and deliberative to reach agreement. Keyword: Nationality Characteristics, Economics Cooperative Learning Model Abstrak: Penelitian ini dilaksanakan dengan tujuan untuk mengembangkan model pembelajaran ekonomi berkarakter kebangsaan dengan pendekatan design based research (DBR). Penelitian ini menggunakan pendekatan model Design Based Research dalam pengembangan Pembelajaran Ekonomi Berkarakter Kebangsaaan Melalui Model Economic Cooperative Learning. Teknik analisis data yang digunakan adalah kuantitatif dengan teknik statistika deskriptif dan kualitatif. Berdasarkan hasil penelitian dan pengembangan menunjukkan hasil tanggapan peserta didik pada saat uji coba di SMA Muhammadiyah Blitar dan di SMA Negeri 1 Rejotangan sebesar 91% dan 95,3%. Hal ini berarti bahwa model pembelajaran Economics Cooperative Learning dapat memahamkan peserta didik tentang konsep ekonomi yang sesuai dengan idiologi Bangsa Indonesia terutama dapat menanamkan nilai-nilai karakter kebangsaan diantaranya, cinta produk Indonesia, menjunjung tinggi kebersamaan, menghargai pendapat orang lain, hemat, bijak dan musyawarah untuk mufakat. Kata kunci: Berkarakter Kebangsaan, Model Economics Cooperative Learning